Analysis Of The Implementation Of Authentic Assessment In The Independent Learning Curriculum In Elementary Schools - Nuryani Nuryani; Faisal Faisal (Jurnal Syntax Admiration, 2023)
Assessment or Assessment is a systematic activity whose process is continuous which is continuously used as a measurement tool for assessing student learning outcomes and as a basis for processing assessment data which is intended as a report on student learning progress ultimately based on certain criteria and considerations for educators. The readiness of symptom evaluation instruments for classroom teachers is an important job to assist in working on the nature of the school, in particular to provide an understanding of demonstrative evaluation, especially to action members, to be specific educators. This article discusses how authentic assessment activities for self-paced curriculum are implemented. The Seven Stages Model Theory of Program Planning and Development is used in service implementation, and qualitative analysis is used in service analysis. The method of reviewing articles and reference sources becomes a supporting instrument. The implementation of the independent curriculum, the introduction of diagnostic assessment, the manufacture of diagnostic assessment instruments, and the analysis of question items are the four topics discussed in the technical guidance material. The advantage that members gain after taking this special assistance is that they can build their insight into the demonstrative evaluations carried out in learning in the learning space; Learn the technical details of diagnostic assessment tests so that they can be used in daily learning, and at least the references are clear enough; Able to understand ongoing curriculum modifications and obtain teaching strategies based on the applicable curriculum.